The Research about Film and Television IP Communication Strategy Based on Short Video Platform - Zhang, Xinyu (Transactions on Social Science, Education and Humanities Research, 2024)
This paper investigates the influence of short video platforms on the dissemination effect of film and television IP. By collecting and analyzing the data of movie box office and its short video dissemination, it is found that the three movies with higher box office have higher heat on short video platforms. From the perspective of communication subject, this paper divides short video communication into two kinds: official publicity and audience spontaneous communication. Further analysis reveals that short video platforms can enable film and TV IP to expand the scope of dissemination, maintain their popularity across media, and increase their commercial value. In the case that the content is high quality, the short video platform can keep the IP hot in a new text form. In addition, this paper also discusses the problems that need to be paid attention to in the dissemination process, like copyright management and over-publicity, and puts forward suggestions. In maintaining a balance between promoting users’ free creation and copyright management, Propaganda subjects should also pay attention to the data feedback and adjust the publicity density.